ADDITION OF MORINGA LEAF (Moringa oleifera) IN RATION CONTAINING RICE HULL AND STARPIG ON BALI DUCKS CARCASS - A. A. A. S., TRISNADEWI; SURANJAYA, I G.; WIRAWAN, I W. (Majalah Ilmiah Peternakan; Vol 24 No 3 (2021): Vol. 24 No. 3 (2021), 2021)
The aim of this study was to determine effect of the addition of Moringa oleifera leaf in ration containing rice hull supplemented with starpig on performnace of bali duck. The study used a randomized block design (RBD) with four treatments included control ration (A), 12.5% ration of rice hull (B), 12.5% ration of rice hull and Moringa leaf (C), 12.5% ration of rice hull, Moringa leaf and starpig (D). Each treatment consisted of four replicate and each rep- licate consist of of four female bali ducks aged 36 weeks. The observed variables egg production and feed conversion ratio. The observed variables were performance, production, and carcass quality. From the results of the study it is expected that the addition of Moringa leaf in the ration containing rice hull supplemented with starpig can im- prove the performance, production, and quality of carcass on bali ducks. Treatment B significantly reduced carcass weight, carcass percentage, and meat, while treatment C and D increased significantly carcass weight, carcass per- centage and meat of bali duck compared to treatment A. Bone and fat including skin decreased with treatment B and treatment C and D showed a significant effect compared to treatment A. The conclusion of the research results that the addition of Moringa oleifera leaf in ration contain rice hull supplemented by starpig could improve carcass weight, carcass percentage, and meat percentage, as well as reduced bone and fat percentages including skin.